Influence of gas fraction on wall-to-liquid heat transfer in dense bubbly flows. (November 2019) - Panda, A.; Weitkamp, Y.E.J.; Rajkotwala, A.H.; Peters, E.A.J.F.; Baltussen, M.W.; Kuipers, J.A.M.
Highlights: Developed a Direct Numerical Simulation method for heat transfer. Included periodic boundary conditions for wall-to-liquid heat transfer. Heat transfer enhancement is caused by a sharpening of the boundary layer. For single bubbles the enhancement is mainly located near the wake. For bubble swarms the heat transfer is correlated to the distance to the wall. Abstract: Bubbly flows are used in industrial processes to facilitate efficient mass and heat transfer for gas-liquid contact operations accompanied by chemical transformations, which are often associated with substantial heat liberation due to exothermic reactions. In this paper we study the heat transfer enhancement from a hot wall to bulk liquid, in the presence of bubbles. We use computational fluid dynamics, and specifically apply the local front reconstruction method as interface-tracking method. When a single bubble rises near a wall, the thermal boundary layer is sharpened enhancing heat transfer. This enhancement is initially located near the equator of the bubble, and then shifts to the wake of the bubble. Using stream wise periodic boundary conditions for flow and heat transfer, the wall-to-liquid heat transfer for developed flow conditions is quantified as function of gas fraction. The enhancement is strongly correlated with the relative bubble distance from the wall.